Analisis Persiapan Dinas Perindustrian Dan Perdagangan Kabupaten Deli Serdang Untuk Mengikuti Kegiatan INACRAFT 2023 - Siti Zahra Khostamarul Aspia Lubis; Nuri Aslami (Master Manajemen, 2024)
This research aims to analyze the preparations of the Department of Industry and Trade of Deli Serdang Regency in participating in Inacraft 2023 activities. The research method used is qualitative analysis, case studies by conducting interviews and observations of related parties. The results of the research show that the Department of Industry and Trade of Deli Serdang Regency has not made thorough preparations, including in terms of product preparation and human resources. There are several obstacles faced, such as budget limitations and limited human resources. Therefore, it is recommended that the Department of Industry and Trade of Deli Serdang Regency continue to improve internal and external coordination, as well as utilize existing resources optimally to ensure the success of their participation in Inacraft 2023 activities.